Long-term efficient deammonification operation with PVA/alginate carrier modified by foaming agent - Khan, M. Hammad; Choi, Daehee; Cho, Kyungjin; Jung, Jinyoung (Elsevier BV, 2018)
This study investigated long-term deammonification operation, of 400 days, utilizing PVA/alginate carriers prepared with the addition of foaming agent (FA) adjusted from 0 to 1.2% (F-0 to F-1.2). FTIR spectra showed variations in the extent of crosslinking in the surface and the core areas of carriers. FA addition improved the already low crosslinking in the core areas and porosity in the surface areas, yielding higher endurance to internally produced gas. In the start-up period of continuous test, FA addition favored deammonification bacteria over denitrifiers. Increasing the FA decreased the extent and duration of heterotrophic denitrification that was superseded by deammonification after 30 d of operation. After 100 d, F-0.6 had the highest deammonification to denitrification ratio and gave a nitrogen removal rate (NRR) of 3.2 kg N.m(-3).d(-1) at 317 d of operation. Also, the 16S rRNA gene concentration of the deammonification bacteria was highest in F-0.6, which corresponded with the specific anammox activity (SAA) results. Overall, the improved PVA/alginate carriers gave higher SAA and deammonification bacteria concentration resulting in a stable long-term deammonification operation with high NRR.